2015
DOI: 10.1007/s00382-015-2671-5
|View full text |Cite
|
Sign up to set email alerts
|

Preferred response of the East Asian summer monsoon to local and non-local anthropogenic sulphur dioxide emissions

Abstract: emissions, the large scale pattern of changes in land-sea thermal contrast, atmospheric circulation and local precipitation over East Asia from days 40 onward exhibits similar structures, indicating a preferred response, and suggesting that emissions from both regions likely contributed to the observed weakening of the EASM. Cooling and drying of the troposphere over Asia, together with warming and moistening over the WNP, reduces the land-sea thermal contrast between the Asian continent and surrounding oceans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 64 publications
5
52
0
Order By: Relevance
“…4e). This is consistent with previous studies using other general circulation models with fixed SST (e.g., Jiang et al, 2013;Dong et al, 2016). However, note that the weakening of the EASM in the fast response to SO 4 is too weak to explain the total response of the EASM to SO 4 , especially over eastern China (Fig.…”
Section: Response Of the Easm To So 4 Forcingsupporting
confidence: 93%
“…4e). This is consistent with previous studies using other general circulation models with fixed SST (e.g., Jiang et al, 2013;Dong et al, 2016). However, note that the weakening of the EASM in the fast response to SO 4 is too weak to explain the total response of the EASM to SO 4 , especially over eastern China (Fig.…”
Section: Response Of the Easm To So 4 Forcingsupporting
confidence: 93%
“…The detailed description of the indices was available from the website, and the data quality was checked by the corresponding agencies before their release. These selected indices cover all of the potential factors affecting the climate in China [35,36].…”
Section: Atmospheric Circulation Indexmentioning
confidence: 99%
“…The addition of non-Asian aerosols leads to further suppression of monsoon rainfall over Asia, highlighting the importance of the non-Asian aerosols in changes in Asian summer monsoon circulation and rainfall across Asia. Dong et al (2016a) indicated that aerosol emissions over Asia and Europe both influence the thermal contrast between Asian land and the western North Pacific, leading to a weakening EASM, but through very different processes. Due to the implementation of air quality legislation, AA precursor emissions over both Europe and North America have continuously declined since the 1980s (Smith et al, 2011;Kühn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…East Asia is under both local and non-local influences of AA (e.g., Cowan and Cai, 2011;Dong et al, 2016a). The study of Cowan and Cai (2011) indicated that Asian aerosols lead to a weakening of the EASM through aerosol-radiation and aerosol-cloud interactions (e.g., Twomey, 1977;Rosenfeld et al, 2008).…”
Section: Introductionmentioning
confidence: 99%